Surgical Reconstruction for Buccal Cancer in Eastern Taiwan - 孫宗伯(Tzong-Bor Sun); 李俊達(Jiunn-Tat Lee); 簡守信(Sou-HsinChien) (慈濟醫學雜誌, 1999)
Objective: To clarify and promote the outcome of surgical reconstruction for buccal cancer in eastern Taiwan. Patients and Methods: Eighty patients with buccal cancer had surgery at Buddhist Tzu-Chi General Hospital between December 1989 and August 1997. Charts of them were reviewed retrospectively. Data such as case number, sex, race, betel nut exposure, method of reconstruction, histology and outcome were collected and analyzed. Results: There were 70 male and 10 female patients, 77 of them (96%) had the habit of betel nut chewing. There were only seven aboriginal patients. The ratio between aboriginal and non-aboriginal patients was quite different from the local racial distribution between these ethnic groups in eastern Taiwan. The stages according to the American Joint Committee on Cancer(AJCC) staging ere stage I, 12 (15%); stage II, 22 (28%); stage III, 16 (20%); and stage IV, 30 (37%). Among 54 patients who had surgery more than 2 years, t patients were lost to follow-up. For this group of patients whose minimal follow-up was 2 years ( n=49), the two-year-survival rate for early buccal cancer (stage I and II) was 75.0%, and for advanced disease (stage III and IV) it was 48.3%. Eighty-four reconstruction procedures were undertaken. There were 44 free flaps, 25 pedicle flaps and 15 split-thickness skin grafts. Forty-four percent of patients with local flap reconstructions and 57% of patients with free flap reconstructions had problems of drooling. Eighty-nine percent of patients with local flap reconstructions and 76% of patients with free flap reconstructions had a comprehensible speech. Conclusions: Betel nut chewing did correlate with the development of buccal cancer. Early detection and early surgical resection followed by reconstruction gives the best results in treatment for buccal cancer. Due to improvements in reconstruction techniques, more radical resection procedures could be done.